Psychosocial predictors of mobbing and burnout in para-athletes: Insights for mental health - Yeliz Ay Yıldız; Gokhan Buyukluoglu; Nihan Buyukluoglu; Sabriye Ercan; Aydan Orscelik (PLoS ONE, 2025)
Para-athletes may experience psychological challenges such as mobbing and burnout, which can impair their performance, motivation, and well-being. Despite the inclusive goals of the Paralympic Movement, recent evidence suggests that para-athletes are not immune to negative psychosocial experiences. This study aimed to examine the relationship between mobbing exposure and burnout among para-athletes and to identify demographic and psychological predictors of mobbing. This cross-sectional study included para-athletes aged 18–45 with at least two years of sports experience. Participants completed an online survey including demographic variables, the Negative Acts Questionnaire-Revised (NAQ-R), and the Athlete Burnout Questionnaire (ABQ). Statistical analyses included group comparisons, correlation tests, and linear regression modeling to explore factors associated with mobbing exposure. A total of 93 para-athletes participated. NAQ-R scores varied significantly by age and showed positive correlations with ABQ-PEE (physical/emotional exhaustion) and ABQ-SD (sport devaluation) scores. Regression Analysis, Adjusted R² = 0.296. Model was significant (F(9,83)=4.10, p < 0.001). Significant predictors, ABQ-SD (β = 0.312, p = 0.004), education level (β = 0.278, p = 0.011). Regression analysis revealed that higher ABQ-SD and educational level were significant predictors of increased mobbing exposure. ABQ-SD and education level are key predictors of mobbing and burnout in para-athletes, revealing that negative interpersonal dynamics persist even in para-sport environments. Targeted anti-mobbing strategies and tailored psychological support are essential to protect mental health and enhance the athletic experience.